Comparison of Anatomical Success Between Early and Late Removal of Silicone oil after Retinal Detachment Surgery - Muhammad Abid Javed, Sidrah Latif, Rana Muhammad Mohsin Javaid, Asad Aslam Khan, Tehseen Mahmood Mahju, Farooq Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The objective of the study is to assess the retinal redetachment after early and late removal of silicone oil. Place and Duration of Study: Department of ophthalmology eye unit 3, KEMU /Mayo hospital, Lahore from February 2021 to July 2021 . Study: Quasi experimental trial. Patients and Methods: Time of silicone oil removal of first group (29 patients) at 6 weeks and second group (29 patients) at 12 weeks post-operatively. Presence of 360 barrage laser. The two groups were compared as to the condition of the eye at the time of SOR at 1st day 1st week, 1st months.3rd month following SOR. Inclusion Criteria PPV for rhegemantogenous RD with all types of breaks with silicon oil tamponade, both gender 360 barrage laser. Exclusion criteria bands keratopathy grade c PVR, presence of cataract, GRT, only eye Results: The risk of retinal re-detachment was similar in both groups. Conclusion: The danger of re-detachment was not increased by early removal of silicone oil after six weeks, and higher compliance with the removal period was ensured. In patients who are less likely to follow a procedure for delayed removal, it is especially advised..